Epidemiology of respiratory syncytial virus in hospitalized children over a 9-year period and preventive strategy impact - Lodi, Lorenzo; Catamerò, Francesco; Voarino, Marta; Barbati, Federica; Moriondo, Maria; Nieddu, Francesco; Sarli, Walter Maria; Citera, Francesco; Astorino, Valeria; Pelosi, Caterina; Quaranta, Francesca; Stocco, Silvia; et al. (Frontiers in Pharmacology, 2024)
Respiratory Syncytial Virus (RSV) is the primary cause of respiratory infections and hospitalizations in young children globally, leading to substantial disease burden and mortality. The aim of the present study was to review and provide updates on how the SARS-CoV-2 pandemic have significantly influenced RSV epidemiology on hospitalized children due to RSV infection. A potential impact of the available preventive strategies on the same population were provided.All children aged 0 to 6 years hospitalized at Meyer Children's Hospital IRCCS for RSV infection from September 2014 to March 2023 were retrospectively recorded. Seasonal trends before and after SARS-CoV-2 pandemic, age distribution, ICU admission and co-infections, comorbidities and prematurity were retrieved.Predictions on the number of hospitalizations avoided by the deployment of different preventive strategies were provided.A total of 1262 children with RSV infection were included in the study. The 70% of them had less than 1 yearof-age at the moment of hospitalization and almost 50% less than 3 months. In the post-pandemic seasons, a 317% increase in the number of hospitalizations was recorded with a significant increase in older children compared to the pre-pandemic seasons. ICU support was required for 22% of children, the majority of whom were under 3 months of age. Almost 16% of hospitalized children were born preterm and only 27% of hospitalized children had prior comorbidities. The rate of comorbidities among RSV hospitalized children increased with age. Nirsevimab prophylaxis could have prevented more than 46% of hospitalizations in this cohort. A preventive strategy addressing also children aged 7 months to 6 years of age with co-existing comorbidities would increase that rate above 57%.The identification of RSV hospitalization-related features is informing the decision-maker for the deployment of the wisest preventive approach on a population scale.